Endophytic Potential and Larvicidal Efficacy of Entomopathogenic Fungi against the Spotted Stem Borer, Chilo partellus - Denberu Kebede; Tesfaye Alemu; Tadele Tefera (Psyche: A Journal of Entomology)
Entomopathogenic fungi (EPF) of different genera are known to have the potential to engage in fungus-plant interactions as fungal endophytes. This hidden endophytic interaction offers several advantages to host plants, such as insect pest management. Hence, this study aimed to explore the endophytic potential and virulence of EPF collections after artificial inoculation. A total of 27 EPF isolates from the genera Beauveria and Metarhizium were screened for virulence. Two inoculation methods (leaf and seed dressing) were used to study the endophytic colonisation potential of the selected isolates. There was a significant variation among the tested isolates in their ability to kill C. partellus larvae. Lower mean percentage mortality was recorded for isolates B4, DS-51-21, and B1,9 which scored 28.01%, 32.29%, and 34.58%, respectively. All the screened EPF isolates were able to colonise maize tissues after artificial inoculation, except for APPRC-34GM. The percent colonisation of maize tissues varied with strains, and delivery methods ranged from a minimum of 0% to a maximum of 53%, where the maximum was recorded by S#10H. Larval mortality after feeding maize leaves inoculated with EPF ranged from 18% to 60%. The findings of this study indicated that Beauveria spp. and Metarhizium spp. have the potential to colonise maize after artificially inoculating and translocating from the site of infection. Hence, the potential to move from the site of infection and larvicidal activity after colonisation may give the advantage to manage insect pests acting on the different parts of maize.